Pengaruh Gaya Kepemimpinan dan Komunikasi Interpersonal Terhadap Kepuasan Kerja di PT URC Indonesia - Salsabila Ratu Alta; Nandang Nandang; Rengga Madya Pranata (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine how leadership approaches and patterns of interpersonal communication influence employee job satisfaction at PT URC Indonesia, both separately and jointly. Primary data were gathered from 222 employees through structured questionnaires utilizing a seven-point Semantic Differential Scale (1 = Strongly Disagree to 7 = Strongly Agree). The data were analyzed using multiple linear regression. The measurement instruments met validity and reliability standards, indicated by item correlation values exceeding the critical r value and Cronbach’s Alpha coefficients above 0.80 for all variables. Partial testing (t-test) indicates that leadership style and interpersonal communication each have a positive and statistically significant effect on job satisfaction. Simultaneous testing (F-test) further confirms that both variables collectively exert a significant impact, as shown by an F-value of 122.488, exceeding the F-table value of 3.04, with a significance level of 0.000. The coefficient of determination (R²) of 0.528 indicates that 52.8% of the variance in employee job satisfaction can be attributed to leadership style and interpersonal communication. These findings substantiate the argument that effective leadership conduct and constructive interpersonal communication constitute critical determinants of employee satisfaction within PT URC Indonesia. Accordingly, reinforcing leadership effectiveness and communication quality may serve as a strategic foundation for human resource management policies aimed at sustaining and enhancing employee job satisfaction, particularly within multinational corporate environments.